Gender research in Cauca, Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Gender research in the province of Cauca, Colombia conducted by the Gender & Climate Change team from CIAT/CCAFS. The aim is to create gender sensitive mapping of household farming systems to identify the productive activities, decision-making and resource use.